Glyphosate Herbicide: Reproductive Outcomes and Multigenerational Effects - Milesi, María Mercedes; Lorenz, Virginia; Durando, Milena; Rossetti, María Florencia; Varayoud, Jorgelina (Frontiers in Endocrinology, 2021)
Glyphosate base herbicides (GBHs) are the most widely applied pesticides in the world and are mainly used in association with GBH-tolerant crop varieties. Indiscriminate and negligent use of GBHs has promoted the emergence of glyphosate resistant weeds, and consequently the rise in the use of these herbicides. Glyphosate, the active ingredient of all GBHs, is combined with other chemicals known as co-formulants that enhance the herbicide action. Nowadays, the safety of glyphosate and its formulations remain to be a controversial issue, as evidence is not conclusive whether the adverse effects are caused by GBH or glyphosate, and little is known about the contribution of co-formulants to the toxicity of herbicides. Currently, alarmingly increased levels of glyphosate have been detected in different environmental matrixes and in foodstuff, becoming an issue of social concern. Some in vitro and in vivo studies have shown that glyphosate and its formulations exhibit estrogen-like properties, and growing evidence has indicated they may disrupt normal endocrine function, with adverse consequences for reproductive health. Moreover, multigenerational effects have been reported and epigenetic mechanisms have been proved to be involved in the alterations induced by the herbicide. In this review, we provide an overview of: i) the consumption and alternatives to GBHs, ii) the routes and levels of human exposure to GBHs, iii) the potential estrogenic effects of glyphosate and GBHs in cell culture and animals models, iv) their long-term effects on female fertility and mechanisms of actions, and v) the consequences on health of successive generations.